2003
DOI: 10.1074/jbc.m301426200
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii Cell Wall β-Glucans Initiate Macrophage Inflammatory Responses through NF-κB Activation

Abstract: ␤-Glucans are major structural components of fungi. We have recently reported that the pathogenic fungus Pneumocystis carinii assembles a ␤-glucan-rich cell wall that potently activates alveolar macrophages to release pro-inflammatory cytokines and chemokines. Purified P. carinii ␤-glucans predictably induce both cytokine generation and associated neutrophilic lung inflammation. Herein, we demonstrate that P. carinii ␤-glucaninduced macrophage stimulation results from activation of NF-B. Although analogous to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 58 publications
4
101
1
Order By: Relevance
“…Our current data support earlier studies that dectin-1 serves as a major receptor for fungal ␤-glucans found on DCs and macrophages (29,33,34). Additional recent studies from our laboratory further document the ␤-glucans stimulate macrophages through MyD88-dependent mechanisms (6). Other investigations have demonstrated that dectin-1 may act synergistically with TLR2 to mediate cytokine generation by DCs and macrophages in response to zymosan, a glucan-rich cell wall fraction of yeast (35).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our current data support earlier studies that dectin-1 serves as a major receptor for fungal ␤-glucans found on DCs and macrophages (29,33,34). Additional recent studies from our laboratory further document the ␤-glucans stimulate macrophages through MyD88-dependent mechanisms (6). Other investigations have demonstrated that dectin-1 may act synergistically with TLR2 to mediate cytokine generation by DCs and macrophages in response to zymosan, a glucan-rich cell wall fraction of yeast (35).…”
Section: Discussionsupporting
confidence: 79%
“…The final preparations were assayed for soluble endotoxin with the Limulus amebocyte lysate assay method and found to consistently contain Ͻ0.125 U of endotoxin (5). Our prior studies have further demonstrated that host cell responses to Pneumocystis ␤-glucans occur through mechanisms distinct from those induced by LPS (6). All Pneumocystis ␤-glucan preparations were analyzed for their proinflammatory signaling capacities.…”
Section: Generation Of a Pneumocystis Glucan-rich Cell Wall Isolatementioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Studies with Pneumocystis jiroveci and fungi have demonstrated that ß-glucans can stimulate the release of inflammatory markers, such as IL-1 and TNF-a, through NF-jB activation, trigger fungicidal responses, and generate reactive oxygen intermediates. [29][30][31][32] These observations provide a mechanism by which Candida may play a causal role in the increased inflammatory markers and may potentiate worse clinical outcomes. 33 In a recent study, rats instilled with live Candida albicans developed increased pulmonary TNF-a and increased rates of pseudomonal pneumonia; whereas, rats instilled with normal saline or ethanol destroyed the Candida albicans.…”
Section: Discussionmentioning
confidence: 97%
“…Immunofluorescence was employed to detect translocation of the p65 component of NF-B to the nucleus (Lebron et al, 2003). Briefly, RAW 264.7 macrophages were seeded onto sterile 22 x 22-mm glass cover slips in 6-well tissue culture plates and pretreated with 30μM CAF overnight followed by LPS for 2 hours prior to fixation with 3.7% paraformaldehyde for 30 min at room temperature.…”
Section: Immunohistochemically Analysis Of Nf-b P65 Nuclear Translocmentioning
confidence: 99%